Periodic nanostructures on unpolished substrates and their integration in solar cells. (10th February 2015) - Cornago, I; Dominguez, S; Ezquer, M; Rodríguez, M J; Lagunas, A R; Pérez-Conde, J; Rodriguez, R; Bravo, J
Abstract: We present a novel fabrication process based on laser interference lithography, lift-off and reactive ion etching, which allows us to fabricate periodic nanostructures on photovoltaic substrates with an average root mean square (RMS) roughness of 750 nm. We fabricate nanostructures on unpolished crystalline silicon substrates, which reduces their reflectance 30% as fabricated. When an additional passivation layer is deposited, the light trapping grows, achieving a reflectance reduction of 60%. In addition, we have successfully integrated the nanostructured substrates in silicon wafer–based solar cells following standard processes, achieving a final efficiency of 15.56%.